Konsep Metode Belajar dalam Taklimul Muta'alim Karya Syekh Azzarnuji dan Relevansinya di Era Pendidikan Modern - Liza, Ahmad (Pascasarjana IAIN Lhokseumawe, 2024)
Ta’limul Muta’allim by Shaykh Al-Zarnuji is one of the classical works of Islamic education that presents principles of learning rooted in spirituality, ethics, and practical wisdom. Amid the transformation of modern education characterized by digitalization and evolving learning methods, it is important to revisit the relevance of these classical concepts in shaping meaningful and character-based learning. This study employs a descriptive qualitative approach using library research and comparative analysis methods. Data were collected through a literature review of Ta’limul Muta’allim and various contemporary educational sources. The analysis was conducted systematically through content analysis and source triangulation techniques to identify the relevance of classical principles to the challenges of modern education. The findings indicate that the key concepts in Ta’limul Muta’allim, such as sincere intention, time discipline, consistency, the teacher’s role as a spiritual guide, as well as the methods of practice and discussion, remain highly relevant in addressing current educational challenges. These principles align with active learning approaches, character-based education, and values-oriented pedagogy. The values embedded in Ta’limul Muta’allim strengthen the spiritual, ethical, and reflective dimensions of learning, thereby fostering learners who are not only intellectually competent but also virtuous and capable of facing contemporary challenges with wisdom.